Biases and improvements of the boreal winter–spring equatorial undercurrent in the Indian Ocean in the CMIP5 and CMIP6 models - Li, Junling; Xu, Kang; Wang, Weiqiang; He, Zhuoqi; Huang, Ke (Frontiers in Marine Science, 2023)
In this study, we assess the performance of state-of-the-art coupled models in reproducing the equatorial undercurrent (EUC) in the Indian Ocean (IO), based on the outputs of phase 6 of the Coupled Model Intercomparison Project (CMIP6) models and compared to that in phase 5 (CMIP5). Results show that the CMIP6 models reproduce boreal winter-spring IO EUC more realistically than the CMIP5 models, even though both of them still underestimate the strength of IO EUC compared to observed. This commonly underestimated IO EUC among the models is attributed to the excessive strong and westward-extended cold tongue (CT) in the equatorial Pacific. In the CMIP models, a stronger winter mean CT favors a stronger zonal SST gradient and then forces a strong easterly wind bias over the equatorial western Pacific, which in turn contributes to an accelerated Walker circulation. This enhanced Walker circulation over the Indo-Pacific Ocean directly causes a lower-level westerly wind bias over the equatorial IO and further drives a “shallow west–deep east” thermocline tilt bias, ultimately leading to an excessive weak EUC in the IO via the wind-induced thermocline processes. Compared with the CMIP5 models, the overall improvement of the winter-spring IO EUC strength in the CMIP6 models can be traced back to the improvement in the degree of the strong and westward-extended CT bias. Our result suggests that substantial efforts should be made to reduce the bias in the mean-state equatorial Pacific SST for further improving the simulation and projection of the IO atmospheric and oceanic circulations.